Directed jaya algorithm for delivering nano-robots to cancer area. Issue 16 (9th December 2020) - Ezzat, Doaa; Amin, Safaa; Shedeed, Howida A.; Tolba, Mohamed F.
Abstract: In the last few years, it was proposed to deliver drugs using Nano-robots for treating cancer. This paper compares between two recent and efficient algorithms for delivering Nano-robots to cancer area. These algorithms are Jaya algorithm and Directed Particle Swarm Optimization (DPSO) algorithm. In this paper, we also propose a new hybrid algorithm that combines Jaya and DPSO to speed up the process of Nano-robots delivery. The proposed algorithm is called Directed Jaya (DJaya) algorithm. Experiments have proved that the efficiency of DJaya is higher than both Jaya and DPSO. We show experimentally that DJaya starts delivering Nano-robots earlier than DPSO to facilitate the initiation of the drug release. Also, DJaya finishes delivering Nano-robots earlier than Jaya to complete the drug dose. In addition to this, DJaya groups the Nano-robots together in the target area like DPSO to speed up the drug release process. We finally propose a new strategy for destroying cancer cells efficiently with relatively small number of Nano-robots. This strategy can save 40% of Nano-robots.